Two auxin-responsive domains interact positively to induce expression of the early indoleacetic acid-inducible gene PS-IAA4/5. - Ballas, N (1995)
The plant growth hormone indole-3-acetic acid (IAA) transcriptionally activates expression of several genes in plants. We have previously identified a 164-bp promoter region (-318 to -154) in the PS-IAA4/5 gene that confers IAA inducibility. Linker-scanning mutagenesis across the region has identified two positive domains: domain A (48 bp; -203 to -156) and domain B (44 bp; -299 to -256), responsible for transcriptional activation of PS-IAA4/5 by IAA. Domain A contains the highly conserved sequence 5'-TGTCCCAT-3' found among various IAA-inducible genes and behaves as the major auxin-responsive element. Domain B functions as an enhancer element which may also contain a less efficient auxin-responsive element. The two domains act cooperatively to stimulate transcription; however, tetramerization of domain A or B compensates for the loss of A or B function. The two domains can also mediate IAA-induced transcription from the heterologous cauliflower mosaic virus 35S promoter (-73 to +1). In vivo competition experiments with icosamers of domain A or B show that the domains interact specifically and with different affinities to low abundance, positive transcription factor(s). A model for transcriptional activation of PS-IAA4/5 by IAA is discussed.